Bridging Social Capital And Health Outcomes: The Mediating Role Of Maternal Agency In Stunting Prevention Services In Kendari City, Indonesia - Kamrin, K Kamrin (International Journal of Health Engineering and Technology, 2026)
Stunting remains a persistent public health challenge in developing countries, reflecting not only nutritional deficiencies but also broader social inequalities. This study examines the influence of social capital and social networks on the effectiveness of stunting prevention services, with a particular focus on the mediating role of maternal agency. A quantitative approach using Structural Equation Modeling (SEM-PLS) was applied to data collected from multiple public health centers in Kendari City, Indonesia, complemented by secondary data on stunting cases from 2022 to 2024. The results show that social capital (β = 0.31, p < 0.01) and social networks (β = 0.27, p < 0.01) significantly influence service effectiveness. Maternal agency also has a strong direct effect (β = 0.41, p < 0.001) and mediates the relationship between social determinants and service outcomes. The model explains 74% of the variance in effectiveness (R² = 0.74), indicating strong explanatory power. These findings highlight the importance of integrating social approaches into public health strategies. This study contributes to the literature by proposing an integrated model linking social structures and maternal behavior to health service effectiveness.